Study of the Situation of Venezuelan Emigrants in Ecuador based on NeutroAlgebra - Luis Antonio Rivera Velazco; Janneth Ximena Iglesias Quintana; Carlos Ramiro Hurtado Lomas; Marco Rodrigo Mena Peralta; José Sergio Puig Espinosa (Neutrosophic Sets and Systems, 2021)
Venezuelan migration to neighboring countries in the area is a phenomenon that has been growing in recent years. Ecuador is one of the main countries where migrants who leave Venezuela have gone to reside.They initially arrived in the country as a transit to reach other countries, however, over time many of them decided to settle in Ecuador permanently. Venezuelan migration in our country presents certain characteristics, such as the youth of those who arrive, the high educational level, and the motivation for economic improvement that prompted them to emigrate at first and in a second wave for family reunification. This research aims to apply a survey to know more precisely the economic, social, labor, and humanitarian situation of this sector of migration in the country. We selected a model that uses NeutroAlgebra and is generated by the PROSPECTOR function. PROSPECTOR function is the well-known function used in the classic medical expert system MYCIN, while NeutroAlgebra is an algebra that has at least one NeutroOperation or one NeutroAxiom, where some cases are indeterminate. This model has previously been used in the evaluation of medical care of migrants in Chile. However, unlike the model we are inspired on, here input data are linguistic terms associated with Single-Valued Neutrosophic Numbers, which allows respondents to express more reliably what they want to say.